2022
DOI: 10.1167/iovs.63.5.18
|View full text |Cite
|
Sign up to set email alerts
|

Host Immune Response and Associated Clinical Features in a Primary Cytomegalovirus Eye Infection Model Using Anterior Chamber Inoculation

Abstract: Purpose To investigate the pathogenesis of cytomegalovirus (CMV)-associated anterior segment infection in immunocompetent hosts and evaluate the effects of ganciclovir and glucocorticoid treatment in management of the disease. Methods We used an inoculation model to reproduce CMV anterior segment infection in immunocompetent rats. Flow cytometry, cytokine analysis, histopathological sections, and quantitative polymerase chain reaction were performed to investigate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Common findings include the presence of macrophages, inflammatory cells, and signs of necrosis in transplanted retinal ganglion cells (RGCs) after graft loss. 14 , 19 , 40 – 42 Notably, one study found that perfusion of the postprocurement allograft with preservative solution before donor placement, and anastomosis resulted in decreased expression of phospho-c-Jun (PNJ+), an apoptotic marker. 43 In addition to histologic outcomes, the viability of ocular chambers was assessed, and intraocular pressures between the WET and native eye were found comparable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Common findings include the presence of macrophages, inflammatory cells, and signs of necrosis in transplanted retinal ganglion cells (RGCs) after graft loss. 14 , 19 , 40 – 42 Notably, one study found that perfusion of the postprocurement allograft with preservative solution before donor placement, and anastomosis resulted in decreased expression of phospho-c-Jun (PNJ+), an apoptotic marker. 43 In addition to histologic outcomes, the viability of ocular chambers was assessed, and intraocular pressures between the WET and native eye were found comparable.…”
Section: Resultsmentioning
confidence: 99%
“…Common findings include the presence of macrophages, inflammatory cells, and signs of necrosis in transplanted retinal ganglion cells (RGCs) after graft loss. 14,19,[40][41][42] Notably, one study found that perfusion of the postprocurement allograft PRS Global Open • 2023…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation